Operational verbal memory and differentiate reading’s span in students - Medina C., Nicolas (2009)
The purpose of this work was to analyze the working memory like a cognitive model envolved in lexical tasks and individual differentiation on capacity of Reading. The subjects were 163 students of public and particular schools. In this study we elaborated a new “reading span test” agreement with suggestions from Daneman and Carpenter (1980), adapted to children students. That instrument was correlated with the subtest of Number from WISC, inverted form. The validity assessment between both tests was made with Spearman’s coefficient of correlation. The consequence of that assessment showed rRHO = 0,47; it should prove both tests contain the function of processing (or computation) proper of the working memorysystem. Then, that “reading span test” is an adequate instrument to measure individual differences about capacity of reading only in similar subjects like those we studied.